Transformation of Long-Lived Albino Epipremnum aureum ‘Golden Pothos’ and Restoring Chloroplast Development - Hung, Chiu-Yueh; Zhang, Jianhui; Bhattacharya, Chayanika; Li, Hua; Kittur, Farooqahmed S.; Oldham, Carla E.; Wei, Xiangying; Burkey, Kent O.; Chen, Jianjun; Xie, Jiahua (Frontiers in Plant Science, 2021)
Chloroplasts are organelles responsible for chlorophyll biosynthesis and photosynthesis, which are one of key targets for crop improvement. Elucidating and engineering genes involved in chlorophyll biosynthesis are important approaches for studying chloroplast development and biogenesis as well as developing new crops. In this study, we report a long-lived albino mutant derived from a popular ornamental plant Epipremnum aureum ‘Golden Pothos’ which could be used as a model for analyzing the function of genes involved in chlorophyll biosynthesis and generating colorful plants. Albino mutant plants were isolated from regenerated populations of variegated ‘Golden Pothos’ whose albino phenotype was previously found to be due to impaired expression of EaZIP, encoding Mg-protoporphyrin IX monomethyl ester cyclase. The mutant plants have been maintained in MS medium for 11 years. Using petioles of the mutant plants as explants with a traceable sGFP gene, an efficient transformation system was developed. Overexpressing Arabidopsis CHL27 (a homolog of EaZIP) but not EaZIP in albino plants restored green color and chloroplast development. Interestingly, in addition to the occurrence of plants with solid green color, plants with variegated leaves and pale-yellow leaves were also obtained in the regenerated populations, suggesting that green color restoration might be resulted from the interaction between the gene and environmental factor(s). Nevertheless, our study shows that these long-lived albino plants along with the established efficient transformation system could be used for creating colorful ornamental plants. This system could potentially be used for investigating physiological processes associated with chlorophyll biosynthesis and chloroplast development as well as various biological activities, which are difficult to achieve using green plants.